Beyond Charity: How Zakat Governance in Jember Transforms Social Relations Among Mustahiq - Nurul Widyawati Islami Rahayu; Fauzan; Khamdan Rifa’i; Ahmad Fathor Rosyid (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2025)
Poverty remains a significant challenge to civilization, particularly within Muslim communities. As a fundamental pillar of Islam, zakat serves a crucial role in alleviating poverty and promoting social welfare. This study analyzes and compares zakat governance in two leading institutions in Jember: Amil Zakat Al-Baitul Amien and the Nurul Hayat Foundation, with a specific focus on empowering mustahiq (zakat recipients). Using a qualitative, descriptive approach, the research explores zakat governance practices based on data gathered through interviews with institutional managers, supported by insights from zakat practitioners and academics. The findings indicate that both institutions generally uphold the principles of good zakat governance and operate with professional standards. However, full optimization remains a challenge—particularly for Al-Baitul Amien. Both organizations have adopted digital technologies to improve zakat collection and service delivery, with the Nurul Hayat Foundation demonstrating greater technological integration. Despite its stronger performance, Nurul Hayat still faces areas for improvement, especially in achieving full accountability, transparency, and operational efficiency. Strengthening governance frameworks in both institutions is essential to unlock zakat’s full potential in empowering mustahiq and supporting sustainable socio-economic development